1989
DOI: 10.1159/000226744
|View full text |Cite
|
Sign up to set email alerts
|

Development of Drug Resistance in Cultured Clonogenic Leukemic Blast Cells during the Clinical Course of Myeloblastic Leukemia

Abstract: We studied changes in the drug sensitivity of clonogenic leukemic blast cells from patients with acute myeloblastic leukemia during clinical courses. These cells were assayed using the colony formation technique in methylcellulose culture. Various doses of each of two chemotherapeutic agents, daunorubicin and aclarubicin, were added at the start of culture, and drug sensitivities were measured in terms of percentage inhibition of leukemic blast colony formation. Clonogenic leukemic blast cells became less sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
1993
1993

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…There seem to be three main reasons, apart from our efficient use of anionexchange chromatography, for the relative ease with which we could purify native G-CSF compared with earlier reports from other sources [18,20]. The first reason was that the HTB9 cell line, which had been proved to produce prominent leukemic blast growth activity [1,2,8], was able to produce high day-7 CSF activity (7000-12 000 U/ml) at a very low serum concentration even in our micro-carrier culture system. This meant that the starting material already had a high specific activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There seem to be three main reasons, apart from our efficient use of anionexchange chromatography, for the relative ease with which we could purify native G-CSF compared with earlier reports from other sources [18,20]. The first reason was that the HTB9 cell line, which had been proved to produce prominent leukemic blast growth activity [1,2,8], was able to produce high day-7 CSF activity (7000-12 000 U/ml) at a very low serum concentration even in our micro-carrier culture system. This meant that the starting material already had a high specific activity.…”
Section: Discussionmentioning
confidence: 99%
“…A subclone of human bladder cell line 5637 designated HTB9 was previously reported to secrete very powerful leukemic blast growth-promoting activity [1,2,8]. Our previous study revealed that this activity also stimulated the growth of normal bone-marrow progenitor cells in vitro [23].…”
Section: Introductionmentioning
confidence: 99%